Unleashing Digital Process Innovation with Process Mining: Designing a Training Concept with Action Design Research - Joas, Adrian; Matzner, Martin (Proceedings of the 30th European Conference on Information Systems (ECIS), 2022)
Process mining (PM) is an emerging trend across many industries. To exploit its potential of increased transparency and organizational efficiency, PM needs to be implemented successfully. Due to its specific characteristics, knowledge on the implementation of other information systems cannot be transferred seamlessly. Applying an action design research (ADR) approach in a mixed team with the PM provider Celonis, we develop a training solution to facilitate PM implementation from a thirdparty implementation partner’s perspective. Therefore, we first formulate the problem by investigating challenges in the implementation process. Next, we derive a training concept as an artifact, using the theoretical foundation of IT implementation models. We evaluate the artifact, reflect on, and formalize the learning. The paper contributes to the PM knowledge base by identifying 38 implementation challenges like quantifying the value of PM and transferring those insights into practice by developing a prototype solutio
Keywords: Process mining; Implementation challenges; Action design research; Training